Bovine piRNA-like RNAs are associated with both transposable elements and mRNAs. Issue 3 (March 2017) - Russell, Stewart; Patel, Mehool; Gilchrist, Graham; Stalker, Leanne; Gillis, Daniel; Rosenkranz, David; LaMarre, Jonathan
Abstract : PIWI proteins and their associated piRNAs have been the focus of intensive research in the past decade; therefore, their participation in the maintenance of genomic integrity during spermatogenesis has been well established. Recent studies have suggested important roles for the PIWI/piRNA system outside of gametogenesis, based on the presence of piRNAs and PIWI proteins in several somatic tissues, cancers, and the early embryo. Here, we investigated the small RNA complement present in bovine gonads, gametes, and embryos through next-generation sequencing. A distinct piRNA population was present in the testis as expected. However, we also found a large population of slightly shorter, 24–27 nt piRNA-like RNA (pilRNAs) in pools of oocytes and zygotes. These oocyte and embryo pilRNAs exhibited many of the canonical characteristics of piRNAs including a 1U bias, the presence of a 'ping-pong' signature, genomic clustering, and transposable element targeting. Some of the major transposons targeted by oocyte and zygote pilRNA were from the LINE RTE and ERV1 classes. We also identified pools of pilRNA potentially derived from, or targeted at, specific mRNA sequences. We compared the frequency of these gene-associated pilRNAs to the fold change in the expression of respective mRNAs from two previously reported transcriptome datasets. We observed significant negative correlations between the number of pilRNAs targeting mRNAs, and their fold change in expression between the 4–8 cell and 8–16 cell stages. Together, these results represent one of the first characterizations of the PIWI/piRNA pathway in the translational bovine model, and in the novel context of embryogenesis.